PENGEMBANGAN HANDOUT BERNUANSA KONTEKSTUAL PADA MATERI SISTEM REGULASI MANUSIA UNTUK SMA - Cahyani, Ditha Amanda; ARDI, ARDI; Amri, Erismar (Pendidikan Biologi, 2014)
ABSTRACT The  less  availability of  handout  for  the  Senior  High  School students  had  made  the learning process not  run as  it  was expected. Therefore, a creative and  innovative  effort  was required to  provide learning  materials for Biology subject  especially those related to  Human Regulation System topic. The aim of this research was to produce a contextual-based handout for teaching  Human Regulation System topic for Senior High School students and to  reveal the validity and  practicality of the product. This was a developmental research which used  4-D models. The research findings showed that the handout developed was valid. This could be seen from the result of the validation test done by the lecturers and teachers in which the validation score was 83,13%. The handout was also practical in which the score given by the teachers was84,71% and the score given by the students was 73,67%. Based on these results, it was concludedthat the contextual-based handout developed for teaching Human Regulation System topics forSenior High School students was valid and practical.